2012
DOI: 10.1007/s13201-012-0068-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical characteristics and GIS-based assessment of groundwater quality in the coastal aquifers of Tuticorin corporation, Tamilnadu, India

Abstract: Tuticorin corporation stretches geographically from 8°43 0-8°51 0 N latitude and 78°5 0-78°10 0 E longitude, positioned in the East-West International sea routes on the SouthEast coast of India. The rapid urban developments in the past two decades of Tuticorin have caused depletion of groundwater quantity, and deterioration of quality through excessive consumption and influx of pollutants from natural and anthropogenic activities. The water samples collected in the field were analyzed for electrical conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 10 publications
0
25
0
2
Order By: Relevance
“…The conventional techniques such as trilinear plots, statistical techniques are widely accepted methods to determine the quality of water. The problems of ground water quality are more acute in areas that are coastal, densely populated and thickly industrialized and have shallow groundwater tube wells (Ballukraya and Ravi 1999;Reddy and Subba Rao 2001;Malini et al 2003;Krishna kumar et al 2011;Padmalal et al 2012;Bagyaraj et al 2013;Selvam et al 2013). The present study was carried out for qualitative analysis based on physico-chemical parameters of groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional techniques such as trilinear plots, statistical techniques are widely accepted methods to determine the quality of water. The problems of ground water quality are more acute in areas that are coastal, densely populated and thickly industrialized and have shallow groundwater tube wells (Ballukraya and Ravi 1999;Reddy and Subba Rao 2001;Malini et al 2003;Krishna kumar et al 2011;Padmalal et al 2012;Bagyaraj et al 2013;Selvam et al 2013). The present study was carried out for qualitative analysis based on physico-chemical parameters of groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution maps of WQI were prepared using one special tool of GIS environment which called Inverse Distance Weighted (IDW) technique. IDW referred to as "deterministic interpolation methods because they assign values to locations based on the surrounding measured values and on specified mathematical formulas that determine the smoothness of the resulting surface" [31] [32]. This method uses a defined or selected set of sample points for estimating the output grid cell.…”
Section: Gis and Water Index Modelingmentioning
confidence: 99%
“…Rina et al (2011 and2013) studied hydrogeochemistry of Sabarmati basin including its coastal aquifers. Selvam et al (2013) assessed the groundwater quality around Tuticorin Corporation limits, Tamilnadu vis-a-vis utility of water for different purposes. Sivasubramanian et al (2013) identified the chemical processes that control hydrochemistry in Kadaladi block of Ramanathapuram District, Tamilnadu.…”
Section: Coastal Aquifersmentioning
confidence: 99%